Strong Women to Strengthen Rural Creative Economy - Ana Sopanah; Syamsul Bahri; Indah Dewi Nurhayati; Irfan Fatoni; Rahayu Puji Suci (Trescode Green Organization, 2024)
The mentoring and socialization activities in Jombok Village, Ngantang District, Malang Regency, aim to empower village women in developing the local creative economy. The main objective of this program is to improve women's skills and knowledge in production, marketing, and business management, so that they can optimize local potential and improve their family's welfare. The methods used include planning, implementation, and evaluation. This activity is carried out through workshops, practical training, and focus group discussions, with a participatory approach that actively involves participants. The results of the activity show that participants have significantly improved their skills, especially in digital marketing and small business management. The implementation of this activity has succeeded in encouraging several participants to apply new marketing strategies, which has an impact on increasing sales of their products. Important findings from this activity are the identification of the need for further training and access to better business capital, as well as the importance of infrastructure and technology support for the sustainability of creative businesses.